A Distributed Framework for the Study of Organizational Cognition in Meetings - Jensen, Astrid; Secchi, Davide; Jensen, Thomas Wiben (Frontiers in Psychology, 2022)
This paper proposes an analytical framework for the analysis of organizational cognition that borrows from recent developments within distributed/ecological cognition (DEC). In so doing, we take a case study featuring a decision on a rather trivial topic, i.e. agreeing on a set point in the agenda of a meeting. It is through the analysis of a few minutes of video-recording used in the case that enables us to demonstrate the power of a DEC approach to organizational cognition. Cognitive mechanism, resources, and processes are identified within this framework. Mechanisms are described as ‘socio-material’ (CM1)—where ‘people’ and ‘artifacts’ are the related cognitive resources—and as ‘conceptual’ (CM2)—with ‘group’ identity, ‘topic’ understanding, meaning of ‘procedures’, and perception of ‘time’ as resources. Processes are defined as ‘coupling’, ‘de-coupling’, and ’un-coupled’ depending on the type of relation in place. Finally, the paper presents an agent-based computational simulation to demonstrate the potentials of operationalizing the framework.